196. Impact of BioFire FilmArray® Blood Culture Identification on the Management of Staphylococcus aureus Bacteremia - Nguyen, Kiet (Open Forum Infect Dis, 2019)
BACKGROUND: Staphylococcus aureus bacteremia (SAB) is associated with 30-day mortality rates that are as high as 20 to 40%. In order to reduce mortality and treatment failures, SAB management should include prompt infectious diseases (ID) consult, repeat blood cultures, source control, intravenous antibiotics for the entirety of treatment, and optimal treatment duration. The objective of this study was to determine the impact of BioFire FilmArray® Blood Culture Identification (BCID) on the implementation of these standard of care measures in the management of SAB across a large health system. METHODS: This study was an IRB approved, retrospective chart review evaluating the impact of rapid diagnostics on the management of SAB before and after implementation of BCID. The composite endpoint consisted of mortality at 30 days, persistent SAB (≥7 days), and recurrence of S. aureus infection within 30 days. Patients were included if they were ≥18 years old and at least one blood culture was positive with S. aureus. The pre-BCID period was between September 1, 2016 and March 31, 2017. The post-BCID period was between April 1, 2017 and July 31, 2018. Fisher’s exact test, student’s t-test, and descriptive statistics were used in the analysis. RESULTS: A total of 200 patients met eligibility (pre-BCID, n = 102; post-BCID, n = 98). The composite endpoint was met in 34% of patients in the pre-BCID group and 29% in the post-BCID group (P = 0.45). Mortality at 30 days (17% vs. 17%, P = 1.00), persistent SAB (16% vs. 13%, P = 0.69), and rates of recurrence within 30 days (4% vs. 1%, P = 0.37) were similar between groups. ID consult increased after BCID implementation (83% vs. 92%, P = 0.001). More patients in the post-BCID received appropriate durations of antibiotics (75% vs. 86%, P = 0.04) and had decreased time, in hours, to definitive therapy (7 ± 17 vs. 1 ± 5, P ≤ 0.05). CONCLUSION: The management of SAB after implementation of BCID did not show a decrease in the primary outcome but did show an improved time to appropriate therapy. A larger study is needed to determine whether improved time to appropriate therapy translates to an improvement in patient outcomes. [Image: see text] DISCLOSURES: All authors: No reported disclosures.